Diagnóstico de competências gerenciais em uma instituição pública municipal - Braga, Paula Cavalcante de Alencar (2020)
Based on the changes and challenges that take place in the work environment, this has become a place of learning, providing professionals, both in the private and public areas, with permanent and continuous training, focused on achieving organizational goals, developing skills and improving the quality of service provision to society. In this context, it can be said that training is, therefore, integrated with people management as an organizational strategy, aiming at the development of individual and institutional skills to align them with the achievement of the institutions' strategic objectives. Based on this knowledge, the general objective of this research is outlined, which is to identify the training needs based on the skills gaps in a municipal public institution; and, to achieve it, four specific objectives were defined: (i) to elucidate the necessary competencies for managers of the institution; (ii) to identify the existing competencies in the public servants; (iii) to diagnose gaps in technical and managerial skills and (iv) to highlight training issues based on the gaps identified. As a theoretical foundation this work addresses conceptual aspects of training and management by competencies, as well as presenting some models of management by competencies, emphasizing training in the public sector. The research can be classified as descriptive, applied and in terms of approaching the problem qualitative. The target audience refers to public managers with management positions. The instruments used for data collection were document analysis, semi-structured interviews and the diagnostic questionnaire on the need for training. In terms of results 62 technical skills and 17 managerial skills were identified with gaps, ranging from 6 to 11, requiring specific training; 27 technical competencies and 14 managerial competencies that presented a gap between 12 and 20, indicating a great need for training. Through the diagnosis of competences, 50 training themes associated with competency gaps were identified, indicating the real needs of managers for the development of competencies.